Endovascular treatment of splenic and renal aneurysms. - Vallina-Victorero Vazquez, M; Vaquero Lorenzo, F; Salgado, A; Ramos Gallo, M; Vicente Santiago, M; Lojo Rocamonde, I; Alvarez Fernandez, L (2009)
Four cases (three women and one man) of embolization of visceral artery aneurysms are presented, of which two affected the splenic artery and two the renal artery. The two renal aneurysms were related to hypertension; one of the splenic aneurysms was diagnosed in the context of hypertension, and the other affected a woman of a fertile age. Microguides, microcatheters, and Guglielmi platinum coils, liberated by electrolysis, with different lengths and characteristics, were used. Also, one of the renal aneurysm cases was related to the placing of a stent due to the existence of a stenosis of the renal artery adjacent to the aneurysmatic neck. Immediate occlusion of the aneurysm was achieved in the four cases. Evaluation with nuclear magnetic resonance angiography carried out 3 months later confirmed the sealing of the aneurysm and the patency of the native artery. Currently available devices provide a good therapeutic option for the embolization of visceral aneurysms with low morbidity and mortality rates.